Pengalaman Ibu Dalam Upaya Pengentasan Stunting - Novryanthi, Dhinny; Suryadin, Asep; Hamidah, Ernawati; Lutiyah, Lutiyah; Ayu, Shinta Arini; Aziz, Shovi Nur; Shyfa, Putri (Universitas Malahayati, 2024)
ABSTRACT Nutritional problems occur in every life cycle, starting in the womb, infancy, childhood, adulthood and old age. The first two years of life are a critical period, because there is rapid growth and development. The condition of failure to grow in children under five results in children being too short and not appropriate for their age due to chronic malnutrition, this term we know as stunting. Stunting makes children more susceptible to disease and as adults they are at risk of developing degenerative diseases. The problem of stunting which is an obstacle to children's growth and development will have an impact on intelligence. Stunting also raises concerns for a country because it affects the quality of human resources which are valuable assets. To explore mothers' adaptation experiences in efforts to reduce stunting. This research is qualitative research with a phenomenological design. Where this research begins by paying attention to the phenomenon being studied, various aspects of the subject and the behavior of the object being seen. Participants are people who provide main information and are key information for 5 participants. Participants in this study were aged between 25 years and 34 years who had children under five years old. From the results of this research, three themes were obtained, namely theme 1: Food based on the age of the toddler that the mother gives. This theme describes the type of food that the mother gives to her child as time goes by and as the child's age increases, the texture and type begin to change according to the child's ability to digest. that food. Theme 2: Mother's parenting style is seen from the needs of the toddler. Participants described providing parenting patterns for toddlers based on the needs that participants saw in their own toddlers when the toddlers did not finish their portions of food, when the toddlers were lazy about eating, as well as the mother's parenting patterns to obtain information on maintaining balanced nutrition in toddlers. Theme 3: mothers maintain the health of their toddlers. This third theme explains how mothers maintain the health of their toddlers in an effort to eradicate stunting with the criteria of maintaining cleanliness in toddlers, caring for sick toddlers. Mothers' experiences in efforts to eradicate stunting have a role and influence on the growth and development of toddlers. Keywords: Stunting, Mother's Experience, Efforts To Eradicate Stunting ABSTRAK Masalah gizi terjadi pada setiap siklus kehidupan, dimulai sejak dalam kandungan, bayi, anak, dewasa dan usia lanjut. Periode dua tahun pertama kehidupan merupakan masa kritis, karena terjadi pertumbuhan dan perkembangan yang pesat. Kondisi gagal tumbuh dari anak balita mengakibatkan anak terlalu pendek dan tidak sesuai dengan usianya diakibatkan dari kekurangan gizi kronis, istilah ini kita kenal sebagai stunting. Stunting menyebabkan anak lebih rentan terhadap penyakit dan ketika dewasa berisiko untuk mengidap penyakit degeneratif . Masalah stunting yang menjadi penghambat tumbuh kembang pada anak akan berdampak pada kecerdasan. Stunting juga menimbulkan kekhawatiran bagi sebuah negara karena berpengaruh terhadap kualitas sumber daya manusia yang menjadi aset berharga. Untuk mengeksplorasi pengalaman adaptasi ibu dalam upaya mengentaskan stunting. Penelitian ini merupakan penelitian kualitatif dengan desain fenomenologi. Dimana penelitian ini diawali dnegan memperhatikan fenomena yang diteliti, berbagai aspek subjek dan perilaku objek yang dilihat. Partisipan adalah orang yang memberikan informasi utama dan merupakan infromasi kunci sebanyak 5 partisipan. Partisipan dalam penelitian ini berusia antara 25 tahun sampai dengan 34 tahun yang memiliki anak dengan usia balita. Dari hasil penelitian ini didapatkan tiga tema yaitu tema 1 : Makanan berdasarkan usia balita yang ibu berikan Tema ini mendeskripsikan tentang jenis makanan yang ibu berikan untuk anaknya seiring berjalannya waktu dan peningkatan usia anak mengalami perubahan dan mulai tekstur dan jenis nya sesuai dengan kemampuan anak dalam mencerna makanan tersebut. Tema 2 : Pola Asuh ibu dilihat dari kebutuhan balita. Partisipan mendeskripsikan pemberian pola asuh pada balita dilihat dari kebutuhan yang partisipan lihat pada balita nya sendiri disaat balita tidak menghabiskan porsi makan, disaat anak balita malas makan, serta pola asuh ibu untuk mendapatkan informasi dalam menjaga gizi seimbang pada balita. Tema 3: ibu mempertahankan Kesehatan balita, tema ketiga ini menjelaskan bagaimana ibu mempertahankan Kesehatan balitanya dalam upaya pengentasan stunting dengan kriteria menjaga kebersihan pada diri balita, merawat anak balita sakit. pengalaman ibu dalam upaya pengentasan stunting memiliki peran dan pengaruh bagi pertumbuhan dan perkembangan balita. Kata Kunci: Stunting, Pengalaman Ibu, Upaya Pengentasan Stunting